BARBARA KRYŽAN-STANOJEVIĆ (ur.): INOVACIJE U SLAVENSKIM JEZICIMA: Zagreb: Biblioteka Srednje Europe, 2011. 153 str. - Stramljič Breznik, Irena (Slavia Centralis, 2020)
Review: Barbara Kryžan-Stanojević (ur.): Inovacije u slavenskim jezicimaThe paper presents the collection of scientific papers Inovacije u slavenskim jezicima (Innovations in Slavic Languages), which is the result of the second international scientific meeting organized within the scientific project Suprotstavljanje globalizacije jezika i kultura (2007).
Keywords: Inovacije u slavenskim jezicima; project Suprotstavljanje globalizacije jezika i kultura; international scientific meeting; Barbara Kryžan-Stanojević; Croatian